Future projections of extreme temperature events in Southwest China using nine models in CMIP6 - Li, Xiehui; Chen, Zifan; Wang, Lei; Liu, Huan (Frontiers in Earth Science, 2022)
Southwest China is close to the Qinghai-Tibet Plateau and presents complex topography. This region's climate presents unique characteristics because of the joint influence of South Asian monsoon, East Asian monsoon, and plateau monsoon. Since Southwest China is one of the areas where extreme weather and climate events occur more frequently, it is sensitive and vulnerable to climate change. In the present research, daily temperature observations at 93 weather stations in Southwest China from 1969 to 2020, and data from nine CMIP6 (Coupled Model Intercomparison Project Phase 6) models from 1995 to 2040 were used to calculate the 17 ETIs (Extreme Temperature Indices). Furthermore, we analyzed and compared the annual change rate, temporal and spatial change trend, and mean change of extreme temperature events in Southwest China and four subzones during historical period and under SSP2-4.5 scenario for the next 20 years. The results showed: (1) From 2021 to 2040 and under the SSP2-4.5 scenario, the annual change rate of 17 ETIs in Southwest China showed that extreme cold events will continue to decrease and extreme warm events will continue to increase. (2) Under the SSP2-4.5 scenario in the next 20 years, CSDI will decrease, while WSDI, TMINmean, and TMAXmean will increase. Moreover, the decrease in amplitude of CSDI was smaller than the increase in amplitude of WSDI. The increase amplitude of TMINmean was slightly smaller than that of TMAXmean. The projected WSDI, TMINmean, and TMAXmean obtained with the four models showed an overall increasing trend with respect to space; however, the increasing range fluctuated in different regions. (3) The mean values of 4 ETIs in different subzones for 2021-2040 indicated that the lowest TMINmean and TMAXmean were observed in the ZP (Zoigê Plateau), the highest in the YGP (Yunnan-Guizhou Plateau), and intermediate higher in the SB (Sichuan Basin). Comparing the mean value of the 4 ETIs from 1969 to 2020, results indicated that the persistence and average state of extreme cold and warm events in different subzones showed different future change trends depending on altitude.